Unsuccessful Self-Enucleation in a Schizophrenic Patient - Noam Bar-Yaakov; Romi Noy Achiron; Michael Paul; Asaf Achiron (Case Reports in Ophthalmological Medicine)
Self-enucleation is a very unusual form of self-mutilation directly linked to mental illness. In this case we present a 26-year-old schizophrenic patient who attempted to enucleate his eye with a rollerball pen. Antipsychotic therapy and emergency surgery saved the patient eye and emphasize the importance of quick response and good collaboration between psychiatric and ophthalmic teams.